2017
DOI: 10.1111/all.13182
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of chronic spontaneous urticaria and autoimmune thyroid diseases: A systematic review

Abstract: Patients with chronic spontaneous urticaria (CSU) are widely held to often have other autoimmune disorders, including autoimmune thyroid disease. Here, we systematically evaluated the literature on the prevalence of thyroid autoimmunity in CSU and vice versa. There is a strong link between CSU and elevated levels of IgG antithyroid autoantibodies (AAbs), with most of a large number of studies reporting rates of ≥10%. Levels of IgG against thyroid peroxidase (TPO) are more often elevated in CSU than those of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 159 publications
6
118
0
20
Order By: Relevance
“…Thus, an autoallergy is postulated in which IgE is directed to an element of self . This is supported by studies that have shown that patients with CSU have high levels of IgE autoantibodies such as IgE‐anti‐TPO and IgE‐anti‐dsDNA in their blood . More recently, using array analyses, over 200 IgE‐autoantigens were found in CSU patients that were not present in controls.…”
Section: Purported Mechanisms Of Chronic Urticariamentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, an autoallergy is postulated in which IgE is directed to an element of self . This is supported by studies that have shown that patients with CSU have high levels of IgE autoantibodies such as IgE‐anti‐TPO and IgE‐anti‐dsDNA in their blood . More recently, using array analyses, over 200 IgE‐autoantigens were found in CSU patients that were not present in controls.…”
Section: Purported Mechanisms Of Chronic Urticariamentioning
confidence: 88%
“…Studies showing the presence of IgG‐anti‐IgE and IgG‐anti‐FcεRI antibodies are summarized in Table . The evidence in support of this mechanism of CSU has been reviewed recently . Removal of IgE and subsequent loss of mast cell FcεRI would explain the slow onset of action of omalizumab seen in up to 30% of patients responding to omalizumab .…”
Section: Purported Mechanisms Of Chronic Urticariamentioning
confidence: 99%
“…Subsequent studies showed that IgG antibodies to the patient's own IgE or its high‐affinity receptor (FcεRI) were instrumental in causing basophil and mast cell degranulation in vitro and are believed to be directly relevant to urticaria pathogenesis . This response has been reviewed in detail recently …”
Section: Introductionmentioning
confidence: 99%
“…Condiciones sistémicas mediadas por el complemento (crioglobulinemia, enfermedad del suero), enfermedades del tejido conectivo (lupus eritematoso sistémico), neoplasias (trastornos linfoproliferativos), trastornos endocrinos o terapias hormonales (tumores ováricos y uso de anticonceptivos orales, respectivamente) y autoanticuerpos antitiroideos 13,14 se han correlacionado con UCE. En UCInd hay un grupo heterogéneo de estímulos que incluyen la causa colinérgica y las físicas como frío y calor, presión retardada, dermografismo, sol, agua y vibración.…”
Section: Etiologíaunclassified